A review of traditional uses, phytochemistry and pharmacology of the genus Indigofera. (10th May 2020) - Gerometta, Elise; Grondin, Isabelle; Smadja, Jacqueline; Frederich, Michel; Gauvin-Bialecki, Anne
Abstract: Ethnopharmacological relevance: Indigofera is the third-largest genus in the family of Fabaceae, with approximately 750 species. It is distributed across all tropical regions. Indigofera species are widely employed in traditional medicine all around the world, against many ailments. Thus, based on these medicinal properties, various investigations have been undertaken in order to appraise the pharmacological activities and the chemical composition of these species. A recent paper provides a summary of the phytochemistry and pharmacology of the genus Indigofera . Consequently, this review is a continuation of this previous study by updating some data and adding information about the phylogeny and traditional uses of the genus. Aim of the study: To provide an overview of the phylogeny, traditional uses, phytochemistry, pharmacology and toxicity of the genus Indigofera, and to identify the remaining gaps and thus supply a basis for further investigations. Materials and methods: A review of the literature was performed by consulting scientific databases such as 'ScienceDirect', 'PubMed', 'Google Scholar' and 'SpringerLink' and using the keyword Indigofera . Results: Over 60 Indigofera species are reported in traditional medicine. The uses depend on the country and the species, but similarities have been noticed. Indeed, treatments of gastrointestinal disorders, inflammatory conditions and pain, skin ailments, and respiratory and infectious diseases are recurring. Phytochemical studies have led to the identification of more than 200 compounds, notably flavonoids and terpenoids. Many pharmacological activities have been demonstrated, particularly antimicrobial, cytotoxic and anti-inflammatory activities, and thus allowed to assert most of the traditional uses of the genus. Some active compounds have been isolated and have shown remarkable therapeutic potential, like the alkaloid indirubin, which is currently being clinically trialed. Conclusions: The data on the genus Indigofera are extensive, but gaps still remain. Indeed, some promising species have not been assessed for their phytochemistry and/or pharmacology and thus remain unexplored. Moreover, relatively few active compounds have been isolated and tested for their biological activity, and studies to explain their mechanism of action are nearly inexistent. Furthermore, some pharmacological studies have inappropriate methodologies that make the results difficult to interpret. Consequently, further in-depth and relevant research is required to supplement the knowledge on this wide-ranging genus and to confirm its reported therapeutic potential. Graphical abstract: Image 1